PENGARUH TERPAAN FILM DUA GARIS BIRU TERHADAP SIKAP REMAJA TENTANG PERKAWINAN USIA DINI - Wati Sudiarta, Ni Made Sri Pradnya; Pradipta, Ade Devia; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2021)
84% of adolescents aged 12-17 years in Indonesia have not received sex education. Where the lack of information on reproductive health and sexuality is one of the reasons child marriage continues to occur. The “Dua Garis Biru” Film trying to explain the importance of sex education for the young generation. This film has been watched by more than 2.5 million viewers, although since the teaser was released, it became controversial because of the theme considered taboo in Indonesia. The purpose of this study was to explain how the exposure of the “Dua Garis Biru” film affects adolescent attitude about early marriage. This research was conducted using explanatory quantitative research methods with Uses and Effects theory. The data analysis was carried out by simple linear regression analysis. The results of this study indicate that the “Dua Garis Biru” film exposure could affect the adolescent attitude about early marriage. Keywords: “Dua Garis Biru” Film, Early Marriage, Uses and Effects Theory.